(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose Implementation of quality-of-life standards for patients with secondary glaucoma after surgery. Material and methods Data analysis included secondary surgical glaucoma patients with a time interval of 4 years. Patients were followed up to 3 years after surgery to answer questions related to subjective perceptions after the surgical intervention (pain, discomfort, near vision, distance vision, intermediate vision, and normal activity). We were also interested in the overall quality of life and the effect on the patient’s psyche when performing certain surgical techniques. Results As part of the questionnaire, patients were asked 36 questions. Responses were received from 98 patients. Thirty-five respondents (97.2%) of patients who underwent cyclocryopexy reported tolerable, minimal, or no pain during and immediately after surgery, with the majority of patients reporting minimal pain. Twenty-one patients (58.3%) did not complain of pain until one year after surgery. According to the survey, 16 respondents (25%) had undergone trabeculectomy. Most respondents reported tolerable pain during surgery, minimal pain for 2 weeks after surgery, and no or minimal pain 2 years after surgery. Eleven respondents (68.8%) answered that their eyesight improved in daily life, but the majority of nine (56.3%) did not notice any change in their vision during short-distance movement, short-distance work, or reading. Most serious problems had patients after cyclocryocoagulation or enucleation of the eye globe. Conclusion Secondary glaucoma surgery for every patient should be personalized and tailored to the patient’s every need, taking into account the patient’s current health status, knowledge and skills as well as socioeconomic circumstances.